2018
DOI: 10.1093/ct/qtx003
|View full text |Cite
|
Sign up to set email alerts
|

When the Watchdog Neither Barks Nor Bites: Communication as a Power Resource in Media Policy and Regulation

Abstract: Communication in policymaking and regulation has been of interest to political scientists for the last fifteen years. Lamentably, the conceptualization and analysis of communication in media policymaking and regulation has yet to garner much attention by media policy scholars. Drawing on theories of power and new institutionalism, we address this paucity by introducing a theoretical and methodological approach that centers on the intersection of communication and power in media policymaking. Such a framework i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 62 publications
(94 reference statements)
0
11
0
6
Order By: Relevance
“…Building on this evidence, we argue that chicken meat production provides us with a strategic case study where there is already evidence of public debate and contestation that could reasonably be expected to be reflected in newspaper coverage. Since there are no known strong corporate ties between newspapers and chicken meat production companies, we would not expect the kinds of silences that other authors have found for cases in which news media have a vested interest, such as media policy and regulation (Ali and Puppis 2018). Chicken meat production in the UK provides a strategic case study because it meets the conditions under which we might reasonably expect the newspapers to provide the arena for contestation along the lines of the implications derived from the normative expectations of the Fourth Estate.…”
Section: Case Selectionmentioning
confidence: 94%
See 1 more Smart Citation
“…Building on this evidence, we argue that chicken meat production provides us with a strategic case study where there is already evidence of public debate and contestation that could reasonably be expected to be reflected in newspaper coverage. Since there are no known strong corporate ties between newspapers and chicken meat production companies, we would not expect the kinds of silences that other authors have found for cases in which news media have a vested interest, such as media policy and regulation (Ali and Puppis 2018). Chicken meat production in the UK provides a strategic case study because it meets the conditions under which we might reasonably expect the newspapers to provide the arena for contestation along the lines of the implications derived from the normative expectations of the Fourth Estate.…”
Section: Case Selectionmentioning
confidence: 94%
“…Research on these highly politicized topics has not provided supporting evidence for the conditions necessary for the normative expectations of the Fourth Estate to hold. Studies point to news media organizations' strong incentives to influence media coverage in their own interest in topics related to media policy and regulation, for example (Freedman 2014;Ali and Puppis 2018). Some even argue that it is always in the media's interest to legitimize, naturalize or institutionalize their own authority (Freedman 2014).…”
Section: Case Selectionmentioning
confidence: 99%
“…Accordingly, media policy scholarship's lack of impact on the policymaking process, coupled with the tendency for regulators to privilege legal and econometric analyses over qualitative, critical, and normative research, continues to dominate discussions at conferences and workshops (see Braman, 2003a;Just & Puppis, 2012 for more on these arguments). 2 Many of these concerns revolve around the question and operationalization of power-a concept underdeveloped in the study of media and communication policymaking (Ali & Puppis, 2018). When policy impact is defined solely as "policy change", the power of policymakers to act as gatekeepers may seem insurmountable.…”
Section: Woe In the Fieldmentioning
confidence: 99%
“…Interestingly, just like with the concept of power (Ali & Puppis, 2018), the question of policy impact specifically in the fields of media and communication policy has been relatively underexplored (Braman, 2003a andPuppis, 2012 are exceptions). Most of our literature review, for instance, is drawn from management theory.…”
Section: Praxis and Impactmentioning
confidence: 99%
See 1 more Smart Citation